2012
DOI: 10.1134/s0036024412070163
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the spectral properties of solutions of borofluoride complex of alkylated dipyrromethene and the physicochemical parameters of solvents

Abstract: Spectral and photophysical characteristics of borofluoride complex of alkylated dipyrromethene (Bodipy) are determined by means of absorption and fluorescence electron spectroscopy in various organic solvents. Dependences of the spectral and photophysical characteristics of Bodipy solutions vs. the physico chemical parameters of solvents are obtained by linear regression analysis and the contribution from each parameter to the property under study is determined. It is established that the negative solvatochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The transition from non-polar solvents to polar ethanol is accompanied by the hypsochromic shift for all investigated compounds. The average Stokes shifts of fluorescence (12 -14 nm) for investigated molecules are higher than the shift of BODIPY compounds with H-substituents in 8-position and approximately equal to commercial CH 3 -substituted analogies [21,22]. It is associated with the increase of the ability to dissipate energy by rotational and vibrational relaxation.…”
Section: Photophysical Characteristicsmentioning
confidence: 91%
“…The transition from non-polar solvents to polar ethanol is accompanied by the hypsochromic shift for all investigated compounds. The average Stokes shifts of fluorescence (12 -14 nm) for investigated molecules are higher than the shift of BODIPY compounds with H-substituents in 8-position and approximately equal to commercial CH 3 -substituted analogies [21,22]. It is associated with the increase of the ability to dissipate energy by rotational and vibrational relaxation.…”
Section: Photophysical Characteristicsmentioning
confidence: 91%
“…In this sense, the relationship between the spectral properties of alkylated BODIPYs in solution and the physicochemical parameters of various solvents is of interest. 78 Marfin et al established that a negative solvatochromic effect is intrinsic for BODIPY. They also concluded that specific interactions contribute substantially to the properties of the chromophore, which are determined by the electron donor properties of the solvent.…”
Section: Synthetic Aspects and Photophysical Tuning Of Dpmsmentioning
confidence: 99%